FUT2 non‐secretor status is associated with Type 1 diabetes susceptibility in Japanese children. Issue 4 (15th December 2016) - Ihara, K.; Fukano, C.; Ayabe, T.; Fukami, M.; Ogata, T.; Kawamura, T.; Urakami, T.; Kikuchi, N.; Yokota, I.; Takemoto, K.; Mukai, T.; Nishii, A.; et al.
Abstract: Aim: To examine the contribution of the FUT2 gene and ABO blood type to the development of Type 1 diabetes in Japanese children. Methods: We analysed FUT2 variants and ABO genotypes in a total of 531 Japanese children diagnosed with Type 1 diabetes and 448 control subjects. The possible association of FUT2 variants and ABO genotypes with the onset of Type 1 diabetes was statistically examined. Results: The se2 genotype (c.385A>T) of the FUT2 gene was found to confer susceptibility to Type 1A diabetes in a recessive effects model [odds ratio for se2/se2, 1.68 (95% CI 1.20–2.35); corrected P value = 0.0075]. Conclusions: The FUT2 gene contributed to the development of Type 1 diabetes in the present cohort of Japanese children. What's new?: This study suggests that the previously reported susceptibility gene, FUT2, contributes to the development of autoimmune Type 1 diabetes in Japanese children.